Principles of cost accounting : managerial applications - Rayburn, Letricia Gayle (Homewood, Ill. : R.D. Irwin, 1983)
This study allows instructors flexibility in the chapter materials presented. The first 11 chapters discuss cost accounting principles and concepts concerned with the collection of cost. The last part of the book emphasizes the application of cost principles and quantitative tools to decision making.
Rev. ed. of: Principles of cost accounting with managerial applications. 1979.
Includes index.
ne 05/03/2020
Loans
Keywords: Cost accounting; Managerial accounting